Preclinical Validation of SilkBridgeTM for Peripheral Nerve Regeneration - Fregnan, Federica; Muratori, Luisa; Bassani, Giulia A.; Crosio, Alessandro; Biagiotti, Marco; Vincoli, Valentina; Carta, Giacomo; Pierimarchi, Pasquale; Geuna, Stefano; Alessandrino, Antonio; Freddi, Giuliano; Ronchi, Giulia (Frontiers in Bioengineering and Biotechnology, 2020)
Silk fibroin (Bombyx mori) was used to manufacture a nerve conduit (SilkBridge) characterized by a novel 3D architecture. The wall of the conduit consists of two electrospun layers (inner and outer) and one textile layer (middle), perfectly integrated at the structural and functional level. The manufacturing technology conferred high compression strength on the device, thus meeting clinical requirements for physiological and pathological compressive stresses. As demonstrated in a previous work, the silk material has proven to be able to provide a valid substrate for cells to grow on, differentiate and start the fundamental cellular regenerative activities in vitro and, in vivo, at the short time point of 2 weeks, to allow the starting of regenerative processes in terms of good integration with the surrounding tissues and colonization of the wall layers and of the lumen with several cell types. In the present study, a 10 mm long gap in the median nerve was repaired with 12 mm SilkBridge conduit and evaluated at middle (4 weeks) and at longer time points (12 and 24 weeks). The SilkBridge conduit led to a very good functional and morphological recovery of the median nerve, similar to that observed with the reference autograft nerve reconstruction procedure. Taken together, all these results demonstrated that SilkBridge has an optimized balance of biomechanical and biological properties, which allowed proceeding with a first-in-human clinical study aimed at evaluating safety and effectiveness of using the device for the reconstruction of digital nerve defects in humans.